A STUDY ON TEACHING-LEARNING PROCESS OF READING USING COGNITIVE CODE LEARNING TO THE FIRST YEAR STUDENTS OF SMA MUHAMMMADIYAH 5 JUWIRING - W I N A R S I H , W I N A R S I H (2007)
This paper is conducted to know the procedure of teaching English adopting the Cognitive Code Learning (CCL). It is aimed to describe the process of teaching reading using CCL, to discover the problems faced by the teacher and students, and to identify the students' opinion on the implemention of CCL in teaching learning process of English. The writer takes the English teacher and students of the first year students of class X especially X A as the subject of the study. The primary data are mainly taken from observation and interview. The secondary data are obtained from teaching material and information about teaching learning pro cess the English teacher. The data are analyzed by using descriptive qualitative method. After analyzing data, the writer draws some conclusions. The first, the procedures of teaching learning process of reading using CCL are 1) engage; it is point where teacher tries to arose the students' interest to the materials 2) study; it is the session where the students are asked to focus the material, 3) activate; it is the section where the teacher describes classroom activities designed to the students. The second, the problems faced by teacher using CCL are that the students lack in the vocabulary, but they are active to ask the teacher. With this method the student can be active because the teacher always gives keyword to stimulate the cognitive ability of the students so that the students know the meaning of words in text without consulting dictionary. The students are more enthusiastic in studying the materials. Students could learn reading effectively. The third, some of the students agree and others disagree with the method used by teacher with their own reason. The students loved this method, so they did not feel bored, but more enthusiastic to follow the teaching learning process.